Manajemen Pemerintah Daerah Dalam Penyediaan Ruang Publik Taman Kota Sebagai Ruang Terbuka Hijau Berkelanjutan Di Kecamatan Bandung Wetan - Yulianti, Susi; Sri Kartini, Dede (Universitas Serang Raya, 2025)
This study aims to analyze the role of local government management in the provision of urban park public spaces as part of sustainable Green Open Space (GOS) in Bandung Wetan District, Bandung City. GOS plays a vital role in enhancing environmental quality and urban community well-being. This research employs a descriptive qualitative method using literature review and secondary data documentation obtained from journals, regulations, and visual observation of urban parks. The findings indicate that although the number of urban parks in Bandung Wetan District is relatively high (59 parks), their quality and sustainability in terms of management remain challenging. Several parks have not fully fulfilled their ecological, social, and aesthetic functions in accordance with sustainability principles. Key issues include weak planning that fails to consider environmental carrying capacity, overlapping institutional coordination, limited facilities, and a lack of monitoring and community participation. Therefore, it is essential to strengthen integrated planning, enhance cross-sectoral coordination, optimize the use of governmental resources, and implement participatory oversight to support the sustainability of urban parks as functional and inclusive green open spaces. This study recommends the development of adaptive and collaborative management strategies to address both ecological and social challenges in urban areas. Keywords: Local Government Management, Urban Parks, Green Open Space, Sustainability, Bandung Wetan.